Effectiveness of fertilisation of seed crops of switchgrass - Rytchenko, А.; Kulyk, М. (Scientific Progress & Innovations, 2024)
Today, the most pressing issue for the development of the Ukrainian economy and reduction of energy dependence is a comprehensive study and rapid implementation of alternative energy sources. Plant energy is the most affordable and annually renewable among the existing renewable energy sources. It is obtained from the phytomass of various energy crops. One of these plants is switchgrass (Panicum virgatum L.), which is the most widely studied. This is due to its plasticity, adaptive properties, simplified cultivation technology and high biomass yield. However, the peculiarities of the formation of seed productivity of this crop have not been fully studied. In this regard, we conducted long-term research in the central part of the Forest-Steppe of Ukraine. The aim of the research was to determine the effect of fertilising seed crops with the chelated preparation ʼKristalon Specialʼ on the formation of plant biometric parameters and seed productivity of switchgrass. The material for the research was the switchgrass variety ‘Zorianeʼ. The experiment was a two-factor one, which included: factor A – the year of the vegetation of the crop (2021–2023) and factor B – variants of spring fertilisation of switchgrass with the chelated preparation ‘Kristalon Special’ of different concentrations (from 10 % to 100 %, respectively, of the recommended application rate). As a result of the research, a significant increase in the biometric parameters of the generative part of switchgrass compared to the control was found. This was observed in the variants of application with 60 % of the working solution of ʼKristalon Specialʼ. They recorded a significant increase in: flag leaf length (up to 45.3 cm), panicle length (up to 35.0 cm) and the number of panicles (4.7 pcs./plant). As a result, these variants significantly increased seed productivity by seed weight (up to 0.077 g/plant) and increased the yield of germinating seeds (up to 62.3 %). The correlation and regression analysis revealed that the seed productivity of switchgrass is in close direct correlation with the biometric parameters of the generative part of plants with a correlation coefficient of r ˃ 0.71. Thus, applying foliar fertilization of crops with 60% of the working solution of ʻKristalon Specialʼ in the spring tillering phase is the most effective among the experimental variants, which has a significant effect on the biometric parameters of the generative part of plants, as well as on increasing seed productivity and germination rate of switchgrass variety ‘Zorianeʼ.